2004
DOI: 10.1007/s00441-004-0907-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of cholinergic cells in retinas of various mouse strains

Abstract: We examined cholinergic cells in the retinas of BALB/C albino, C57BL/6J black, and 129/SvJ light chinchilla mice by using immunocytochemistry with specific antisera against choline acetyltransferase (ChAT). Two types of ChAT-immunoreactive amacrine cell bodies were found in the inner nuclear layer (INL) and ganglion cell layer in the retinas of all three mouse strains. They were distributed with mirror-image symmetry and their processes ramified in strata 2 and 4 of the inner plexiform layer. A distinct type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…There are also reports that nAChR expression differs among mouse strains in other brain regions which includes an age-dependent component. For example, a substantial (2-fold) strain-specific variability in nAChR expression is observed in the striatum (Altavista et al, 1987) as well as the retina (Kang et al, 2004) and cerebellum (Turner and Kellar, 2005). Further, a dynamic relationship between nAChR expression by CA1 neurons and astrocytes has also been suggested to be found throughout the life span of both rodents and humans (Hosli et al, 2000;Graham et al, 2002;Graham et al, 2003;Teaktong et al, 2004;Gahring et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports that nAChR expression differs among mouse strains in other brain regions which includes an age-dependent component. For example, a substantial (2-fold) strain-specific variability in nAChR expression is observed in the striatum (Altavista et al, 1987) as well as the retina (Kang et al, 2004) and cerebellum (Turner and Kellar, 2005). Further, a dynamic relationship between nAChR expression by CA1 neurons and astrocytes has also been suggested to be found throughout the life span of both rodents and humans (Hosli et al, 2000;Graham et al, 2002;Graham et al, 2003;Teaktong et al, 2004;Gahring et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The immunogen for the ChAT affinity-purified antibody was human placental enzyme. The antibody has been characterized extensively in mouse retinal tissue (see Kang et al, 2004;Heinze et al, 2007), and has been shown to label an expected 68 -70-kD band in immunoblots (Brunelli et al, 2005). Retinas were then rinsed in PBS and incubated in donkey antigoat IgG conjugated to Cy2 (at 1:200; Jackson ImmunoResearch, West Grove, PA) overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Rod and (putative) ONcone bipolar cells were immunostained with a mouse monoclonal antibody against G-protein Go␣ (Haverkamp and Wä ssle, 2000). Cholinergic amacrine cells were labeled with a goat polyclonal antibody against choline acetyltransferase (ChAT) (Jeon et al, 1998;Haverkamp and Wä ssle, 2000;Kang et al, 2004). RGCs including their dendrites and axons were immunolabeled with a mouse monoclonal antibody against tubulin, ␤III isoform (Sharma and Netland, 2007).…”
Section: Antibodiesmentioning
confidence: 99%